An implementation plan of total maximum daily load (TMDL) and water quality modelling approach at the Melaka River, Malaysia - Siti 'Ai'syah, Che Osmi (2019)
Melaka River has become one of the most popular places for tourism attraction and has been listed as historical and heritage of UNESCO in July 2008. However, the rapid development, urbanisation and tourism activities gave negative impact to the Melaka River, such as several cases of fish kills incident, smelly and black color of river has been reported. Thus, an effective strategy needs to be developed to ensure the pollution enters the river is accountable and manageable. The research aims to study maximum amount of pollutant allowed to enter the river, within the water quality standard by implementing the total maximum daily loads (TMDL) approach at Melaka River, Malaysia. The TMDL approach at Melaka River, has been carried out with the water quality assessment and water quality modelling as the planning tools. This work has been done by collecting the water quality data and hydraulic data from the four times water quality sampling and data from the government agency. The physicochemical data were collected and analyses. The physical parameter which is conductivity, salinity, temperature, and total suspended solids (TSS) were collected in this study. Besides, the chemical parameter such as biochemical oxygen demand (BOD), chemical oxygen demand (COD), dissolved oxygen (DO), total phosphorus (TP), phosphate (PO43-), total nitrogen (TN), and ammoniacal nitrogen (NH3-N) were also studied. The COD concentration (365.54 mg/L). was found out as the highest parameter contributed into the river especially at the downstream. From the Water quality index (WQI) analysis have classified the Melaka River under Class III river. Therefore, TMDL for the Melaka River was assigned to achieved Class IIB, which suitable for recreational activities with body contact. The Pearson correlation analysis shows strong significant positive correlation occurs between COD and DO (r-value 0.520, 0.669), COD and TP (r-value 0.606), and COD and TSS (r-value 0.740, 0.975, 0.608), and strong significant negative correlation between COD and BOD (r-value -0.545). This shows that the improvement of COD during the TMDL approach, can significantly improve the other parameters, as well as the water quality of Melaka River. There were 10 scenarios created for COD loads reduction analysis by using InfoWorks River Simulation (RS) as the planning tools for TMDL approach, and Scenario 9 was selected as the optimum condition to achieved Class IIB at Melaka River, with the TMDL is 21387.30 kg/day, WLA is 8131.99 kg/day and MOS is 2138.73 kg/day. The control strategies at point sources and nonpoint sources were suggested. The point sources control strategies were suggested to implement the treatment plant with a combination of A2O (Anaerobic/Anoxic/Oxic) and SBR (sequencing batch reactor) system, while the nonpoint sources control was proposed to apply the Best Management Practices (BMPs) systems. The effective monitoring program, and time frame were proposed to evaluate the effectiveness and successfulness of TMDL approach. Besides, from the survey analysis, shows that even though 69% of stakeholders have knowledge on TMDL, however, only 2 % has deeper understanding on the TMDL process. Whereas 59% of stakeholders believes that the implementation of TMDL approach will significantly impact the governing body and economy. The future challenges need to face in terms of fundamental and involvement of stakeholders was discussed in this study. In conclusion, the result presented in these studies may facilitate to improve the water quality of the Melaka River, as well as initiated the TMDL implementation plan approach in Malaysia